An agent-based clustering framework for reliable satellite networks. (August 2021) - Geng, Sunyue; Liu, Sifeng; Fang, Zhigeng; Gao, Su
Abstract: Agent technique is applied to deal with varying demands and satellites are specifically modeled as agents with autonomy and responsiveness. While most studies introduce efficient agent-based satellite networks, the efficiency of satellite operation that reflects network performance needs to be quantified. Moreover, it is still difficult to configure and manage large-scale networks with existing frameworks as a result of resource limitations. This paper proposes a practical framework for satellite networks to solve these issues by means of agent-based modeling, clustering technique and game theory. An agent hierarchical structure including three control levels is designed for single satellite to manage components. According to the structure, a novel indicator named effectiveness is presented for efficiency assessment. A clustering network framework is proposed to guarantee the stability and scalability, leading to lifetime maximization in resource–critical situations. Furthermore, a collaborative routing scheme based on the Nash bargaining solution is introduced to obtain the globally optimal route. Case analysis shows that the superiority of the proposed framework compared with state-of-the-art algorithms in terms of reliability improvement and energy efficiency while maintaining low network delay. Highlights: An agent hierarchical structure is introduced to analyze satellite operation. An evaluation indicator is presented to quantify satellite efficiency. A fresh clustering framework suitable for large-scale satellite networks is proposed.